Rotenone Protects Against Acetaminophen-Induced Kidney Injury by Attenuating Oxidative Stress and Inflammation - Hu Hua; Xuhua Ge; Mengqiu Wu; Chunhua Zhu; Lihong Chen; Guangrui Yang; Yue Zhang; Songming Huang; Aihua Zhang; Zhanjun Jia (Karger Publishers, 2018)
Background/Aims: In clinic, excessive acetaminophen (APAP) can cause kidney damage with uncertain mechanisms. Recently, accumulating evidence demonstrated a pathogenic role of mitochondrial dysfunction in the kidney injury. Thus, in this study, rotenone, a mitochondrial complex I inhibitor, was applied to the mice with APAP-induced acute kidney injury to evaluate the effect of mitochondrial complex I inhibition on APAP nephrotoxicity. Methods: After 3 days of rotenone pretreatment, mice were administered with APAP (300mg/kg) by intraperitoneal injection for 24 h. Then the kidney injury, inflammation, and oxidative stress were evaluated. Results: APAP significantly enhanced the BUN, serum creatine, and cystatin C levels in line with a moderate alteration of renal morphology. Strikingly, rotenone treatment normalized BUN, serum creatinine, and cystatin C levels, as well as the kidney morphology. Meanwhile, APAP enhanced tubular injury markers of NGAL and KIM-1 by 347- and 5-fold at mRNA levels, respectively. By Western blotting, we confirmed a 15-fold increment of NGAL in APAP-exposed kidneys. Importantly, rotenone treatment largely normalized NGAL and KIM-1 levels and attenuated inflammatory response in APAP-treated mice. Similarly, rotenone treatment enhanced the expressions of SOD1-3 compared with APAP group in line with a significant suppression of kidney MDA content. Finally, we observed that inhibition of mitochondrial complex III failed to protect against APAP-induced nephrotoxicity. Conclusion: Mitochondrial complex I inhibitor rotenone protected kidneys against APAP-induced injury possibly via the inhibition of mitochondrial oxidative stress and inflammation.